Expanding trauma education during war: pediatric trauma fundamentals training in Ukraine - David Mills; David Mills; David Mills; Alexis Schmid; Alexis Schmid; David Lewander; Michelle Gonnet; Oleksii Lopatniuk; Oleksandra Demetska; Olena Sorokina; Anna Bolonska; Ramona Sunderwirth; et al. (Frontiers Media S.A., 2024)
IntroductionOn 24 February 2022, Russia launched a large-scale offensive in Ukraine, resulting in significant casualties to civilians, including children. As part of a seven-stream trauma education initiative, a novel pediatric trauma fundamentals course (PTF) was developed to provide standalone pediatric trauma education by our academic/NGO partnership. The objective of the program was to develop, implement, and evaluate a novel PTF educational course in the active armed conflict zone of Ukraine.MethodsA novel two-day PTF course was internally developed, translated into Ukrainian, and implemented across eight Oblasts (regions) in Ukraine from November 2022 to December 2023. Participants completed pre-and post-assessments in knowledge and self-confidence, and critical skills were assessed against objective skill checklists. Change in knowledge and self-confidence were analyzed, respectively, with the nonparametric Wilcoxon matched-pairs signed-rank test and McNemar's test for paired data. Anonymous course evaluations were solicited after each course. Six to eight-week follow-up surveys were conducted to assess skill utilization and stewardship.ResultsFour hundred and forty-six Ukrainian health care providers were trained during 30 courses across 8 Oblasts in Ukraine during the intervention period. Aggregated knowledge and self-confidence significantly improved across all measures. Ukrainian instructors of courses received higher raw scores across all evaluation points on instructor feedback surveys as compared to international instructors. Six to eight-week follow-up surveys demonstrated participants had positive views of the training, have used the training on patients, and have taught the material to other health care providers.DiscussionOur novel PTF intervention demonstrates a successful partnership-based model for implementing pediatric trauma education in an active conflict zone in Ukraine. Challenges to implementing such programs can be mitigated through strategic partnership-based models between academic institutions and organizations with local knowledge and expertise. Ukrainian instructors provide course experiences similar or superior to international instructors, likely due to multiple factors related to language, culture, and context.